Epidemiology of Psoriasis and Comorbid Diseases: A Narrative Review - Bu, Jin; Ding, Ruilian; Zhou, Liangjia; Chen, Xiangming; Shen, Erxia (Frontiers in Immunology, 2022)
Psoriasis is a chronic autoimmune inflammatory disease that remains active for a long period even lifetime in most patients. The impact of psoriasis on health is not only limited to the skin, but also influences multiple systems of the body, even mental health. With the increasing of literature on association between psoriasis and extracutaneous systems, a better understanding of psoriasis as an autoimmune disease with systemic inflammation is created. Except of cardiometabolic diseases, gastrointestinal diseases, chronic kidney diseases, malignancy, infections that have received much attention, the association between psoriasis and more systemic diseases, including skin system, reproductive system, oral and ocular systems, has also been revealed, and mental health diseases draw more attention not just because of the mental and mood negative influence caused by skin lesions, but a common immune-inflammatory mechanism identified of the two systemic diseases. This review summarizes the epidemiological evidence supporting the association between psoriasis and important and/or new-reported systemic diseases in the past five years, and may help to comprehensively recognize the comorbidity burden related to psoriasis, further to improve the management on the persons with psoriasis.